Indeks Kepuasan Masyarakat sebagai Instrumen Evaluasi dan Perencanaan CSR PT INALUM pada Program Hikayat Si Kuta di Desa Kuala Tanjung - Jenny Dwi Herawati; Prity Nurpazirah; Racha Julian Chairurrizal; M. Alex Ridwan; Effendi Ibrahim (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to measure the Community Satisfaction Index for PT INALUM's CSR program in Kuala Tanjung Village, Batu Bara Regency, North Sumatra Province. The Hikayat Si Kuta program serves as an evaluation instrument and basis for sustainable planning, which contributes significantly to improving the community's quality of life through an integrated program of education, training, and local capacity building. The research approach uses a quantitative method by distributing a Community Satisfaction Index questionnaire to program recipients. The study results show high satisfaction scores in most aspects, but there are critical challenges in the program's independence and sustainability, indicating potential dependency. This is because one of the programs has only been running for 1-2 years, so in the early stages the impact of its independence is not yet clearly visible. These findings confirm that corporate social responsibility (CSR) has had a tangible impact, but strategies are still needed to strengthen the program's social resilience. This article recommends the development of a roadmap for strengthening the capacity of assisted groups so that the implementation of corporate social responsibility (CSR) programs can have a more sustainable and inclusive impact.